Stellar winds of hot stars. Issue 69 (10th September 2015) - Stee, Ph.; Chesneau, O.
Abstract : In this paper, we summarize the basic properties of radiative stellar winds from the theoretical and observational point of views. We illustrate two examples of a radiative code applied to stellar physics: the SIMECA code successfully used to constrain the physics of the circumstellar environment of the Be star α Arae constrained by VLTI-AMBER spectrally resolved measurements and the CMFGEN code applied to the BA supergiants Deneb and Rigel constrained by CHARA-VEGA measurements.